The knife markets of Sanaa - Waring, Rob; Heinle Cengage Learning (London : Heinle, Cengage Learning/National Geographic, 2008)
Sanaa is a beautiful old city in the Middle East. In Sanaa, it is a tradition to carry beautiful knives, or tools, called'jambiya'. An unusual animal called a'rhinoceros' is often killed to make these knives. How can people keep their tradition and save the rhinoceros?
Video and audio on DVD
Title from container
Pre-intermediate 1000 headwords
DVD format
Optional audio and subtitle in American English or British English
Keywords: Geography